دور التكوين الجامعي في تفعيل النية المقاولاتية لدى الطلبة (دراسة ميدانية لعينة من الطلبة بجامعة ورقلة) - خميس, نفيسة; محسن, عواطف (جامعة الوادي - University of Eloued, 2017)
We aim through this study is to investigate the contributions of the university formation in activating the entrepreneurial intentions among students, as well as to identify whether the knowledge and qualifications that offered by the university formation allows the student to proceed at his own project, where the study was conducted on a sample made up of 113 students who will graduate in different disciplines: management sciences, Applied sciences and agricultural sciences at different levels at the University of Ouargla, where we adopted in data collection on the questionnaire and analyzed it by the statistical program SPSS v.19.The study have reached as results that the university formation contributes to the activation of intention entrepreneurial but the personality traits did not affect the entrepreneurial intention of the student, and there are differences in the entrepreneurial intention between disciplines, while the gender, the academic level and professional experience did not make any differences in the entrepreneurial intention
The Role Of University Formation In Activating The Students’ Intention Entrepreneurial (A field study of a sample of students at the University of Ouargla)
مقال
Keywords: تكوين جامعي ؛ نية مقاولاتية ؛ طلبة مقبلين على التخرج ؛ سمات شخصية.; university formation, entrepreneurial intention, personality traits